A shallow-living benthic Rhodaliid siphonophore: citizen science discovery from Papua New Guinea - Mańko, Maciej K.; Weydmann, Agata; Mapstone, Gillian M. (Zootaxa, 2017)
Benthic siphonophores of the family Rhodaliidae (Cnidaria, Hydrozoa) are extremely fragile, difficult to collect, and therefore little studied. Only a few records exist worldwide, so their ecology remains largely unknown. Rhodaliids have been found at most depth horizons, but until now were believed to mainly inhabit deeper water over continental shelves, with only a few records from ca. 100 m. In this paper, a new rhodaliid is described based on an underwater photograph provided by a recreational diver via Facebook. This observation was made in Milne Bay (Papua New Guinea) at a depth of 26–27 m, and constitutes the shallowest record so far for any rhodaliid. The specimen was tentatively identified as Archangelopsis typica based on observable morphological characters and an approximate estimate of connectivity between all rhodaliid species in the Indo-Pacific region. Additionally, we highlight the scientific potential of citizen science.